Numerical and analytical investigation of Jeffrey nanofluid convective flow in magnetic field by FEM and AGM - Mohammad ِDehghan Afifi; Ali Jahangiri; Mohammad Ameri (International Journal of Thermofluids)
In the present research, a numerical and analytical study on magnetohydrodynamic (MHD) convective flow of Jeffrey nanofluid has been presented. Investigation of mass and heat transfer phenomena has been done using mathematical modeling and considering thermal radiation. Solving and developing non-linear differential equations is done using finite element method (FEM) and Akbari-Ganji method (AGM). The novelty of this research lies in its application of these methods to investigate the effects of varying physical parameters on Jeffrey nanofluid flow, thereby filling a significant gap in the field of magnetohydrodynamics (MHD). Non-linear equations for energy, momentum and concentration are converted into dimensionless nonlinear equations by using appropriate variables. The main goal of this study is to determine the effect of various physical parameters on velocity, temperature and fluid concentration with the finite element model. This particular model was chosen because of the important role of magnetohydrodynamics and its wide applications in industry, engineering and medicine. The obtained results are presented graphically. It can be seen that with the increase of the mixed convection parameter, the velocity field increases, but the temperature and concentration decrease. Increasing the Hartmann number increases the speed and decreases the temperature in a certain range. When the Prandtl number increases, the temperature decreases. An increase in the Schmidt number results in a decrease in concentration. The results of the present study are in good agreement with the previous results, which shows the high accuracy and efficiency of the techniques used in this study.